Analysis of the correctness of problems in the mechanics of inelastic deformation with the influence of a stressed state on the processes of radiation swelling and radiation creep of the material - Chirkov, O. Yu. (Reports of the National Academy of Sciences of Ukraine, 2021)
Modern models of radiation swelling and radiation creep of irradiated materials are considered, taking the damaging dose and irradiation temperature into account. The constitutive equations are formulated that allow describing the non-isothermal processes of inelastic deformation of the material with regard for the radiation effects of hardening, swelling, and creep. Analysis of properties of the constitutive equations made it possible to formulate conditions under which the power of dissipation and the power developed by additional stresses on additional deformations do not decrease under neutron irradiation loading conditions. On the basis of the obtained energy inequalities, which generalize Drucker’s postulate in relation to the irradiated material, conditions are established that ensure the correctness of the radiation creep equations. A priori estimates of the maximally permissible value of the damaging dose for austenitic steel for various irradiation temperatures are given. In the practice of strength calculations, the obtained estimates can be useful at the stage of setting the problem for analyzing the adequacy of the initial data.